First molecular genotyping of insensitive acetylcholinesterase associated with malathion resistance in Culex quinquefasciatus Say populations in Malaysia - Low, V.L.; Chen, Chee Dhang; Lim, P.E.; Lee, H.L.; Lim, Y.A.L.; Tan, T.K.; Sofian-Azirun, Mohd (2013)
Background: Given that there is limited available information on the insensitive acetylcholinesterase in insect species in Malaysia, the present study aims to detect the presence of G119S mutation in the acetylcholinesterase gene of Culex quinquefasciatus from 14 residential areas across 13 states and a federal territory in Malaysia. Results: The ace-1 sequence and PCR-RFLP test revealed the presence of glycine-serine ace-1 mutation in the wild populations of Cx. quinquefasciatus. Both direct sequencing and PCR-RFLP methods demonstrated similar results and revealed the presence of a heterozygous genotype at a very low frequency (18 out of 140 individuals), while a homozygous resistant genotype was not detected across any study site in Malaysia. In addition, statistical analysis also revealed that malathion resistance is associated with the frequency of ace-1R in Cx. quinquefasciatus populations. Conclusion: This study has demonstrated the first field-evolved instance of G119S mutation in Malaysian populations. Molecular identification of insensitive acetylcholinesterase provides significant insights into the evolution and adaptation of the Malaysian Cx. quinquefasciatus populations. Â© 2013 Society of Chemical Industry.